Effect of esophagogastric devascularization with splenectomy on schistossomal portal hypertension patients' immunity - Ferreira,Fabio Gonçalves (2007)
BACKGROUND: Surgical treatment of hemorrhagic complication in schistosomal portal hypertension in our hospital is an esophagogastric devascularization procedure with splenectomy. Infectious risks and immunological alterations imputed to splenectomy may have significant importance. To minimize the consequences of spleen absence, the use of subtotal splenectomy and spleen auto-transplantation were stimulated. AIM: To verify the immunologic alterations imposed by this procedure in our patients. METHOD: Twenty-eight patients with schistosomal portal hypertension and previous history of upper digestive bleeding due to esophagogastric varices rupture underwent elective esophagogastric devascularization and splenectomy. They were prospectively studied before esophagogastric devascularization procedure with splenectomy, 15 and 30 days, 3 and 6 months after the procedure. T and B-lymphocytes, CD4 and CD8 subpopulations were determinated by monoclonal antibodies. Immunoglobulins A, M, G and C3, C4 components of the complement were determinated by radial immunodiffusion. RESULTS: We observed important reduction of all immune cells, increase of IgG and normal levels of IgM, IgA, C3 and C4 at preoperative. CD4/CD8 relation was normal. Six months after esophagogastric devascularization procedure with splenectomy, significant increase in T-lymphocytes, CD4, CD8 and B-lymphocytes were observed. CD4/CD8 relation remained normal. We noted significant increase in C3. IgA, IgM, IgG and C4 had increased, but without significant difference. CONCLUSION: Esophagogastric devascularization procedure with splenectomy determines an increase in T and B-lymphocytes, CD4 and CD8 subpopulations without compromising immunoglobulins and components of complement levels.